Biochemical mechanisms towards understanding Alzheimer's disease - Padayachee, Eden Rebecca (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2014)
The start of the amyloidogenic pathway in Alzheimer's disease (AD) begins with the deposition of the AÎ²â‚ â‚‹â‚„â‚‚ peptide surrounded by astrocytes. High levels of arginine and low amounts of neuronal nitric oxide synthase (nNOS) are associated with AD. These astrocytes store reserve arginine that is eventually metabolized by nNOS, within the vicinity of the AÎ²â‚ â‚‹â‚„â‚‚ peptide. We propose the existence of an association vs. dissociation equilibrium between AÎ² and nNOS such that nNOS is an amyloidogenic catalyst for fibrils. When AÎ² binds to nNOS, it inhibits the activity of the enzyme (association phase). However when the amyloid peptide dissociates into a form that can no longer bind, later deduced as a fibril, the activity is restored. Thus, the interaction of AÎ² with nNOS could serve to regulate the interaction between nNOS and arginine by restoring activity of the enzyme but at the same time promoting fibrillogenesis. Given this event occurring with the neuron, both nNOS and amyloid can serve as a biomarker for the early onset of AD. The enzyme nNOS catalyzed the formation of fibrils in the presence of AÎ² peptides, while Ag nps were shown to reverse the fibril formation from AÎ² peptides more so than Au and curcumin either through electrostatic or Ï€-Ï€ stacking (aromatic) influences. Our studies have shown that the fragments of AÎ²â‚ â‚‹â‚„â‚‚ i.e. the pentapeptide (AÎ²â‚ â‚‡â‚‹â‚‚â‚ ) and the three glycine zipper peptides (AÎ²â‚‚â‚…â‚‹â‚‚â‚‰, AÎ²â‚‚â‚‰â‚‹â‚ƒâ‚ƒ, AÎ²â‚ƒâ‚ƒâ‚‹â‚ƒâ‚‡) and the full length glycine zipper stretch (AÎ²â‚‚â‚…â‚‹â‚ƒâ‚‡) all inhibited nNOS activity to varying degrees. The peptides AÎ²â‚ â‚‡â‚‹â‚‚â‚ and AÎ²â‚‚â‚‰â‚‹â‚ƒâ‚ƒ with their respective Ki values of 5.1 Î¼M and 7.5 Î¼M inhibited the enzyme the most. The Ki values for reversed sequenced peptides (AÎ²â‚ â‚‡â‚‹â‚‚â‚ r and AÎ²â‚‚â‚‰â‚‹â‚ƒâ‚ƒr) were two fold greater than that of the original peptides while the Ki values for the polar forms (AÎ²â‚ â‚‡â‚‹â‚‚â‚ p and AÎ²â‚‚â‚‰â‚‹â‚ƒâ‚ƒp) were between 3-4 fold greater than that of the original peptides. It was also found that Ag nps (Ki = 0.12 Î¼M) inhibited the activity of nNOS the most compared to Au nps; (Ki = 0.15 Î¼M) and curcumin (Ki = 0.25 Î¼M). At 298K, all the ligands bound at a single site on the enzyme (n=1) and a single Trp residue (Î¸ =1), (later identified as Trp678) was made available on the enzyme surface for quenching by the ligands. Increasing the temperature from 298K-313K, increased the value of Ksv and pointed to a dynamic quenching mechanism for AÎ² peptides, nps and curcumin interaction with nNOS. The positive signs for entropy and enthalpy for all AÎ² peptides nps and curcumin pointed to hydrophobic"“hydrophobic interaction with the enzyme. The fact that Kd increased with temperature emphasized the endothermic nature of the binding reaction and the requirement of thermal energy to aid in diffusion of the ligand to the active site. It was concluded that the binding reaction between the ligands and nNOS was non-spontaneous and endothermic at low temperatures (+Î”G) but spontaneous at high temperatures (-Î”G). The two amino acids Tyr706 and Trp678 moved from their original positions, subject to ligand binding. Trp678 moved a minimum distance of 5 Ã… toward the heme while Tyr706 moved a maximum distance of 14 Ã… away from the heme. AutoDock 4.2 was a valuable tool in monitoring the distance of Trp678 within the enzyme interior and fluorescence resonance energy transfer (FRET) was efficient in monitoring the distance moved by Trp residues on the enzyme surface.
Keywords: Alzheimer's disease; Nitric-oxide synthase; Biochemical markers; Amyloid beta-protein; Peptide hormones